How unconventional are large-scale asset purchases? The impact of monetary policy on asset prices - Carlo Rosa (Federal Reserve Bank of New York, 2012)
This paper examines the impact of large-scale asset purchases (LSAP) on U.S. asset prices (nominal and inflation-indexed bonds, stocks, and U.S. dollar spot exchange rates) using an event study with intraday data. The surprise component of LSAP announcements is identified from Financial Times articles. Estimation results show that the LSAP news has economically large and highly significant effects on asset prices, even after controlling for the surprise component of the Fed's conventional target rate decision and communication about its future path of policy. This study documents that the cumulative financial market impact of the Fed's LSAP program is equivalent to an unanticipated cut in the federal funds target rate that ranges between zero (for three-month yields) and 197 basis points (for ten-year yields), with the response of stock prices and foreign exchanges lying within this interval. These point estimates are, however, surrounded by considerable uncertainty. By looking at the cross-asset reactions, this work concludes that, for most U.S. asset prices, the effects of asset purchases are not statistically different from an unanticipated cut in the fed funds target rate. Finally, the response of U.K. asset prices (excepting FTSE 100 stocks) to the Bank of England's gilt purchases is quantitatively similar to the reaction of U.S. asset prices to the Fed's asset purchases.
Keywords: C14; E52; E58; F31; 330; U.S. Federal Reserve; Bank of England; large-scale asset purchases; high-frequency data